Nonconformance in Electromechanical Output Relays of Microprocessor-Based Protection Devices under Actual Operating Conditions - Gurevich, V. (Електротехніка і електромеханіка, 2006)
Microprocessor-based protection relays are gradually driving out traditional electromechanical and even electronic protection devices from virtually all fields of power and electrical engineering. In this paper, one of many problems of microprocessor-based relays is discussed: nonconformance of miniature electromechanical output relays under actual operation conditions: switching inductive loads (with tripping CB coils or lockout relay coils) at 220 VDC, and "dry" switching of some control circuits. We suggest a simple and very reliable solution to this problem: an electronic amplifier for increase in switching ability of the output relays. Мікропроцесорні реле захисту швидко витісняють традиційні електромеханічні і навіть електронні пристрої захисту практично у всіх областях електроенергетики. У статті розглядається одна з численних проблем мікропроцесорних реле: невідповідність параметрів вихідних елементів цих реле, виконаних на основі мініатюрних електромеханічних реле, реальним умовам експлуатації: комутації індуктивного навантаження (котушок вимикачів) при напрузі постійного струму 220 В і так звана "суха" комутація кіл управління. Запропоновано простий і надійний підсилювач спеціальної конструкції для збільшення комутаційної спроможності вихідних реле. Микропроцессорные реле защиты быстро вытесняют традиционные электромеханические и даже электронные устройства защиты практически во всех областях электроэнергетики. В статье рассматривается одна из многочисленных проблем микропроцессорных реле: несоответствие параметров выходных элементов этих реле, выполненных на основе миниатюрных электромеханических реле, реальным условиям эксплуатации: коммутации индуктивной нагрузки (катушек выключателей) при напряжении постоянного тока 220 В и так называемая "сухая" коммутация цепей управления. Предложен простой и надежный усилитель специальной конструкции для увеличения коммутационной способности выходных реле.